Evaluation of Calcium Hydroxide, Triple Antibiotic Paste, Mineral Trioxide Aggregate and Biodentine as Pulp Capping Agents in Deep Carious Teeth - Sujan Thapa,; Snigdha Shubham,; Vanita Gautam,; Manisha Nepal,; Rupam Tripathi, (Journal of Universal College of Medical Sciences, 2025)
INTRODUCTIONDeep caries Management (DCM) with a reliable biomaterial is considered an alternative to Root Canal Treatment (RCT) provided the pulp is vital. Calcium Hydroxide (CH) and Mineral Trioxide Aggregate (MTA) are relatively more popular as pulp capping agents. Triple Antibiotic Paste (TAP) has been proposed for lesion sterilization and tissue repair (LSTR). Biodentine is relatively new biomaterial currently explored for vital pulp therapy.MATERIAL AND METHODSA total of 100 cases confirmed eligible for pulp capping were randomly assigned to either CH, TAP, MTA or Biodentine group (25 teeth per group). The allocated pulp capping agent was applied followed by Glass Ionomer Cement. Permanent restoration was done with composite at 3rd week. Clinical and radiographic evaluations were performed at 3 weeks, 3 months, 6 months and 1 year. Teeth presenting with severe pain or no response to pulp sensibility tests or demonstrating periapical changes in the radiograph were considered failures.RESULTSBiodentine and MTA had 22 (31.9%) successful cases each. CH had 13 (18.8%) successful cases and TAP had 12 (17.4%). There was statistically significant difference in the pain score between Biodentine and CH, between Biodentine and TAP at 6 months. There was statistically significant difference in the vitality of the teeth for the pulp capping materials at 3 weeks while no significant difference in the radiographic findings.CONCLUSIONBiodentine and MTA showed better outcome than CH and TAP based on subjective symptoms, pulp sensibility tests and radiographic findings. Thus, Biodentine and MTA can be used as replacement for CH and TAP as pulp capping material.